1990
DOI: 10.1039/ft9908603159
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of n-hexane over EUROPT-1: fragments and C6products on fresh and partially deactivated catalyst

Abstract: The reactions of n-hexane have been studied on 6.3% Pt/SiO, (EUROPT-1) at different hydrogen and n-hexane pressures, and at 543-633 K, over fresh catalyst and over catalysts deactivated by long runs. Turnover numbers are compared with literature data: the differences are attributed to hydrogen pressure effects. Deactivation influences first of all, selectivity. In addition, the 'depth' and ' pattern' of hydrogenolysis have been determined.At low temperature multiple splitting s e e m s to be favoured. lsomeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…The results obtained with another Pt black (Pt-HCHO, BET surface, 2.64 m 2 g −1 , dispersion D = 1.6% [6]) were very similar, thus they will not be tackled in detail here. The supported catalysts were: 6% Pt/SiO 2 , known as EUROPT-1 [23], D = 60%; 2%; Pt/CeO 2 calcined at 773 K, corresponding to 2Pt-Ce HTR in Ref. [26], D = 35%.…”
Section: Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained with another Pt black (Pt-HCHO, BET surface, 2.64 m 2 g −1 , dispersion D = 1.6% [6]) were very similar, thus they will not be tackled in detail here. The supported catalysts were: 6% Pt/SiO 2 , known as EUROPT-1 [23], D = 60%; 2%; Pt/CeO 2 calcined at 773 K, corresponding to 2Pt-Ce HTR in Ref. [26], D = 35%.…”
Section: Catalystsmentioning
confidence: 99%
“…The differences are conspicuous. The main products were MCP and isomers with much less fragments [20] and [23]. Deactivation slightly increased the MCP selectivity at the expense of isomerization.…”
Section: Activities and Selectivities In Standard Test Runsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond-shift mechanism in addition to isomerization gives also the hydrogenolysis reaction being this latter the preferred one. On platinum catalysts the cyclic mechanism prevails over the bond-shift producing isomerization, dehydrogenative C 5 -cyclation and aromatization (via C 5 -cycle enlargement) [32] and it seems that the selectivity pattern of our monometallic Pt catalysts support this route of reaction. It has been showed that the cyclic intermediate is flatly chemisorbed on the platinum surface requiring ensembles of platinum atoms of certain size and disposition [33,34].…”
Section: Selectivity Of N-hexane Reactionmentioning
confidence: 99%
“…Considering similar reaction conditions, the M f values for different forms of Pd catalysts were reported as close to 2 [22,23] whereas M f for Pt catalysts was usually much higher, often approaching a level of ca. fivefold higher [22,24]. Figure 3 shows results obtained for n-hexane hydrogenolysis over Pd-Pt/Al 2 O 3 catalysts prereduced at different conditions.…”
Section: Resultsmentioning
confidence: 99%